fog(x) = f(g(x)) fog(x) = 4(x² + 8x - 2) - 1 fog(x) = 4x² + 32x - 8 - 1 fog(x) = 4x² + 32x - 9 cari fog(2) fog(2) = 4(2)² + 32 (2) - 9 fog(2) = 4(4) + 64 - 9 fog(2) = 16 + 64 - 9 fog(2) = 71
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
fog(x) = f(g(x))
fog(x) = 4(x² + 8x - 2) - 1
fog(x) = 4x² + 32x - 8 - 1
fog(x) = 4x² + 32x - 9
cari fog(2)
fog(2) = 4(2)² + 32 (2) - 9
fog(2) = 4(4) + 64 - 9
fog(2) = 16 + 64 - 9
fog(2) = 71
f (x) = (g⁻(x))² + 7(g⁻(x)) + 2 ---> g(x) = x+2
y = x+2
x = y-2
g⁻(x) = x-2
f(x) = (x-2)² + 7(x-2) + 2
= (x²-4x+4)+(7x-14)+2
= x²+3x-8